Tubulin Polymerization Promoting Protein, Ringmaker, and MAP1B Homolog Futsch Coordinate Microtubule Organization and Synaptic Growth - Shi, Qian; Lin, Yong Qi; Saliba, Afaf; Xie, Jing; Neely, G. Gregory; Banerjee, Swati (Frontiers in Cellular Neuroscience, 2019)
Drosophila Ringmaker (Ringer) is homologous to the human Tubulin Polymerization Promoting Proteins (TPPPs) that are implicated in the stabilization and bundling of microtubules (MTs) that are particularly important for neurons and are also implicated in synaptic organization and plasticity. No in vivo functional data exist that have addressed the role of TPPP in synapse organization in any system. Here, we present the phenotypic and functional characterization of ringer mutants during Drosophila larval neuromuscular junction (NMJ) synaptic development. ringer mutants show reduced synaptic growth and transmission and display phenotypic similarities and genetic interactions with the Drosophila homolog of vertebrate Microtubule Associated Protein (MAP)1B, futsch. Immunohistochemical and biochemical analyses show that individual and combined loss of Ringer and Futsch cause a significant reduction in MT loops at the NMJs and reduced acetylated-tubulin levels. Presynaptic over-expression of Ringer and Futsch causes elevated levels of acetylated-tubulin and significant increase in NMJ MT loops. These results indicate that Ringer and Futsch regulate synaptic MT organization in addition to synaptic growth. Together our findings may inform studies on the close mammalian homolog, TPPP, and provide insights into the role of MTs and associated proteins in synapse growth and organization.